Pediatric cataracts: Epidemiological, etiological, and clinical profiles in Morocco - Loulidi, Soukaina; Elbahi, Youssef; Boussaa, Samia; Loukid, Mohamed (International Journal of Public Health Science (IJPHS), 2025)
Cataracts are a prevalent eye disease in children, particularly in the congenital form. Its occurrence is the primary cause of avoidable blindness and visual impairment. Our study aimed to assess the epidemiological characteristics and spatiotemporal distribution of infantile cataracts in children from the Marrakech-Safi region. A retrospective study was carried out in the Mohammed VI University Hospital. Data collection, carried out between March 25, 2024, and April 26, 2024, was based on a review of the medical records of sick children aged between 0 and 15 years and having undergone surgery between 2019 and 2023. The findings revealed a high rate of cataract in boys (64.7%), with congenital cataract predominating (57.6%), followed by traumatic cataract (41.1%). In 2021, 81 cases of cataracts were reported, with 51.5% of cases being bilateral. Cataract development (42.4%) was attributed to postnatal and infantile factors, with the remaining 42.7% having an unknown etiological. The study revealed a significant association between cataract type and factors such as gender, age, residence area, age at onset of cataract, consanguinity, and family history. Efficient, high-quality care can prevent cataract complications. This can be achieved by implementing health strategies targeting all levels of prevention.